La carnalidad del amor: percepción e historia - Dillon, Martín (1997)
This essay endeavors to develop at heory of erotic love based on Merleau-Ponty's thesis of the reversibility of flesh. It is specitically directed toward the cognitive aspects of sex love in the attempt todistinguish authentic love from romantic love, and to elaborate the role of camal knowledge in responding to erotic anxiety. The ancient Greek themes of mimesis and nobility (to kalón) are redefined through the concepts of reversibility and transfer of corporeal schema to generate a theoretical understanding of the roles of perception and embodimentin the historical unfolding oferotic incorporeity and reveal the values implicit therein.